Evolutionary theory of higher-level strategic thinking - Loh, Poh Yong (2015)
This paper aims to develop the evolutionary theory of higher-level strategic thinking.Particularly, it focuses on the relationship between the survival of level-k strategic thinkers and the stability of the environment in which the evolution occurs and the cost of thinking.The results illustrate that the more stable the environment, the less favorable the survival of higher-level strategic thinkers, and vice versa. In addition, the smaller the cost of thinking, the more advantageous to be higher-level strategic thinkers, vice versa. Last but not least,from the simulation results, when the environment is extremely unstable, we observe the coexistence of both level-1 and level-2 thinkers, suggesting individual’s strategic thinking is complementary to that of their opponents.